Inclination of Mandibular Molars and Alveolar Bone in Untreated Adults and Its Relationship with Facial Type - Yun Jeong Lee; Hyeran Helen Jeon; Normand Boucher; Chun-Hsi Chung (Applied Sciences, 2022)
To date, there is no solid agreement on the relationship between mandibular molars, mandibular alveolar bone, and vertical facial types. Therefore, we aim to assess the buccolingual inclination of mandibular first molars and respective alveolar bones and their relationship with different vertical skeletal patterns. The CBCT data from fifty-four untreated Caucasian adult patients (12 males and 42 females, 18–65 years old) were obtained from a private orthodontic practice. We measured the inclination of the tooth and alveolar bone of the right and left mandibular first molars using CBCT. From the two-dimensional lateral cephalometric radiographic images extracted from CBCT, we assessed FMA, SN-GoGn, and PFH:AFH. All subjects showed lingual inclinations of the mandibular molars and alveolar bones which were significantly correlated with each other. However, there was no significant correlation between the inclination of alveolar bone and vertical facial types. Our study supports the conclusion that a proper curve of Wilson is physiological and should be maintained during orthodontic treatment.